Synthesis, Characterization, Catalytic Applications and Optical Sensing Properties of Palladium Complexes Containing Tetradentate Schiff Bases - Köse Yaman, P.; Subasi, E.; Temel, H.; Öter, O.; Çelik, E. (Asian Journal of Chemistry, 2014)
In this study, the synthesis, spectroscopic and catalytic properties of PdLn (n = 1-6) complexes with tetradentate -ONNO- and -SNNS- type Schiff base ligands LnH2 (n = 1-6) were investigated. The PdLn (n = 1-6) complexes were synthesized by the thermal reactions of the Schiff bases and Pd(OAc)2 in acetonitrile and characterized by elemental analysis, FT-IR, 1H NMR, UV-visible and TGA/DTG. The spectroscopic studies suggest that all of the ligands are coordinated to the central metal as a tetradentate ligand coordinating via the central azomethine nitrogens (C=N) and phenolic oxygen/sulfur atoms. On the palladium-catalyzed Suzuki cross-coupling reactions employing PdLn (n = 1-6) complexes toward a various substituted arylbromides and boronic acids were pursued. The conversions were obtained and yields with different arylbromides were calculated and discussed. All the complexes were thermally stable and were not sensitive to air or the moisture. The complexes were easily prepared from low cost precursors that could be used as versatile and catalysts for different C-C coupling reactions (Suzuki-Miyaura reactions). Moreover steady state fluorescence emission and excitation spectra were measured. These studies have been shown that PdL2 and PdL3 dyes exhibited high fluorescence intensity and selective and efficient response to cobalt ions over other metal ions in buffered solutions.